Story structure architect : a writer's guide to building dramatic situations and compelling characters. - Schmidt, Victoria Lynn, ....- (Cincinnati (Ohio) : Writer's Digest, 2005)
With Story Structure Architect, writers will discover how to use the classical structures found in all literature since Greek mythology to create unique and successful works. Presented in a fun, 2-colour illustrated design, this book: Walks readers through each step of the structuring process - from identifying characters to building conflict and weaving in unique plotting structures; Offers thousands of possible story combinations with its browsable and interactive index format; Features 56 timeless dramatic situations, plus a blank situation template writers can use as they structure their own work; These techniques apply to every genre, including multicultural storytelling - making this book a must-have resource for anyone who writes short fiction, novels, scripts, plays or even video and role playing games.
Keywords: Scenario's.